Tectonothermal history of the Schwarzwald Ore District (Germany): An apatite triple dating approach - Danisik, Martin; Pfaff, K.; Evans, Noreen; Manoloukos, C.; Staude, S.; McDonald, B.; Markl, G. (Elsevier Science BV, 2010)
Exceptionally large, U-rich apatite from the Schwarzwald ore district (Germany) was triple dated using ID-TIMS U-Pb, fission track (FT) and (U-Th)/He dating methods. The aim of adopting the multi-dating approach on a single sample was to (i) further constrain thermo-tectonic evolution of the Schwarzwald from the formation of crystalline basement through to cooling and exhumation, and (ii) test potential and limitations of in-situ FT-(U-Th)/He double dating.The apatite U-Pb age of 289.5 +/- 4.5 Ma records the cooling of the basement through the 550 degrees C during the Early Permian and brackets the age of the apatite-hosting rhyolite between 289.5 +/- 4.5 Ma and 314 +/- 6 Ma, which is the age of rhyolite-hosting granite. This is in excellent agreement with radiometric ages of related rhyolites and fits with the magmatic evolution of the Schwarzwald during Variscan orogeny. In the Eocene between similar to 50 and 40 Ma, the basement resided at 100 degrees C and then cooled to surface temperatures as revealed by the FT age (37.6 +/- 1.3 Ma) and thermal modelling results based on track lengths.During the cooling event, the basement was likely exhumed as a rift shoulder of newly formed Upper Rhine Graben rift. Nine apatite grains yielded (U-Th)/He ages from 30.7 +/- 1.5 to 65.0 +/- 2.6 Ma (mean age: 45.7 +/- 1.3 Ma). Three possible reasons for the lack of reproducibility are: (i) non-homogeneous distribution of parent isotopes evidenced by strong U zoning, (ii) 'bad neighbourhood causing implantation of extraneous He, and (iii) radiation damage leading to increased He retentivity, implied by the high (>250 ppm) U concentration. These problems could not be circumvented by mechanical abrasion of outermost rim of dated crystals which yielded (U-Th)/He ages from 26.0 +/- 1.0 to 56.2 +/- 2.2 Ma (mean age: 37.2 +/- 1.4 Ma).In-situ FT and traditional (U-Th)/He double dating of single apatite crystals revealed that the vast majority of (U-Th)/He ages were younger than, indistinguishable from or overlap within error with corresponding FT ages, proving the robustness of this approach. The results also show that apparent discrepancies between FT and (U-Th)/He ages reported in the literature may arise simply as a result of statistical misconceptions and conventional data treatment. Considering the range of single grain FT ages and the oldest single grain FT age (in addition to the central FT age), may provide an effective basis on which to evaluate the viability of (U-Th)/He data.